THE UNDERSTANDING OF MILLENNIALS GENERATION BEHAVIOR IN ASEAN - Eldes Willy Filatrovi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Generational gap cannot be avoided in the world of work. Each generation has different characteristics. Cultural differences in Indonesia and western countries also cause differences in habits, behavior, and perspectives. This can cause differences in how to manage employees. This study aims to understand the view of Y generation in Indonesia on motivation, values, leadership, organizational culture, work-life balance, communication, and know what needs to be done to be able to understand and manage Y gene effectively. This research is a qualitative research. The data collected by interview 7 people who work in banking sector. Y generation assume that motivations can comes from external (compensation, insight, experience, career path, incentives) and internal (commitment, humanity, self-impulse). Values consider as respecting promises and rights, doing things in a simple way. Leadership prefered in the form of mentoring and coaching but still given to do the task independently. Organizational culture preferred in the form of technological advancement, casual in dressing and communicating. Work and life is not balanced when measured in terms of time, but satisfaction is obtained from slipping personal life in the middle of work. Communication preferred flexible and not rigid. Based on these perspective, to understand and manage Y generation in Indonesia effectively it should be done from mutual understanding and want to learn from each other's desires and opinions. Keywords: Behavior, Millennials Generation, Values, Work-Life Balance